Analysis of Risk Factors for Antimicrobial Resistance in Nosocomial Pneumonia - Larissa Amanda; Jatu Aphridasari; Yusup Subagio Sutanto (Respiratory Science, 2026)
Background: Antibiotic resistance is often linked to nosocomial pneumonia, one of the most prevalent hospital-acquired illnesses. Determining risk factors is crucial for management and preventative plans. To develop preventative and control measures, this research was conductedto identify the variables linked to antibiotic resistance in nosocomial pneumonia patients. Method: In this retrospective cohort analysis, 237 individuals with nosocomial pneumonia were included. Odds Ratios (OR) were computed for relevant factors after data were evaluated using the chi-square or Fisher’s exact test to find significant relationships between patient characteristics and antibiotic resistance. Results: Of the 237 patients, 58.2% exhibited antibiotic resistance. Several variables were found to be significantly associated with antibiotic resistance: age >59 years (OR=1.68; P=0.049), intensive care unit (ICU) admission (OR=2.65; P=0.002), high care unit (HCU) admission (OR=2.16; P=0.028), history of prior antibiotic use (OR=2.42; P=0.004), and endotracheal tube (ETT) use (OR=2.04; P=0.024). Patients older than 59 years had a 1.68-fold higher risk. Those admitted to the ICU and HCU had 2.65-fold and 2.16-fold higher risks, respectively. Patients with a history of prior antibiotic use had a 2.42-fold increased risk, and those with ETT use had a 2.04-fold increased risk. Conclusion: Older age, admission to intensive care units (ICU/HCU), previous antibiotic use, and endotracheal tube use are significant factors associated with antibiotic resistance in nosocomial pneumonia. These findings highlight key areas for targeted interventions to mitigate resistance.